Kaidah Kualifikasi Intelektual Mufasir dan Urgensinya - Alfurqon, Alfurqon (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2011)
Koran has condemned those who do not pay attention to abortion, and that the companions themselves often do not know or understand the meaning of different opinions in the words of God, so that from their early discussions have arisen in the interpretation of the Koran. Being an authoritative expert on the interpretation of the Koran is a noble task and position. As commentators not only to explain the verses are not clear, but also explain the law and all its consequences as the main guidelines of Muslims. But commentators are not as easy as imagined. There are conditions of knowledge and personality that must be met. This is important because the Prophet himself has given strict guidelines for those who want to interpret the verses of the Koran are not stuck on subjectivity and personal interests. This article tries to discuss the intellectual and personality prerequisites that must be owned by an interpreter as seen by scholars.